Tembakau dan alkohol, manfaat dan mudaratnya - Admar Jas (Fakultas Kedokteran USU, 2013)
Introduction : Tobacco come from crop leaf, tobacum L nicotiana ( fam. solanaceae) representing clump crop. Tobacco leaf which have been dried generally utilized for cigarette, as well as used for the sugi of, antiseptic and insectiside. The special contain of tobacco leaf is nicotine, nikotianin, tar, carbonitril, malic acid and tartaric acid. But from cigarette smoke will be obtained other additional substance like carbon monoxide and carbonitril. Nicotine and nicotianin are alkaloid which in body will stimulate autonom nervous system (ANS) and produced dopamine. The action of dopamine will distors cardiovascular system especially tachicardia, the high pressure of systole and euphoria. But happened high dose on the contrary that is hypotensi because nicotine and nikotianin will bind with nikotinik reseptor, so that happened hypotensi or vasodilatation. Where as carbon monoxide will bind haemoglobin to form the complex which don't have ability to bind oxygen. As a result is the physical become weak. Tar and of carbonitril can trigger the cancer of lung. The effect of tobacco especially nicotine and its derivate with alcohol will be happened an interaction and potentiation’s effect. Both of this compound will be accumulated in brain and lung so that will bother exhalation system and cardiovascular.Keywords : nicotine and it’s derivate; carbon monoxide; tar; from cigarette bothering of cardiovascular and lung syste